2011
DOI: 10.1029/2009jb006660
|View full text |Cite
|
Sign up to set email alerts
|

Velocity modeling of a complex deep crustal structure across the Mesoproterozoic south Delhi Fold Belt, NW India, from joint interpretation of coincident seismic wide-angle and near-offset reflection data: An approach using unusual reflections in wide-angle records

Abstract: [1] Seismic wide-angle record sections from favorably placed source and limited-aperture recording spreads, particularly across collision boundaries, reveal bright unusual highvelocity contrast reflections of limited lateral coherence. The arrival times of the unusual reflections for recording updip of the reflecting plane align as high apparent velocity phases at wide-angle offsets. Coincident near-offset reflection images from similar structural features provide additional control for modeling the unusual ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Contrarily, high-resolution refraction studies with 50-to 100-m shot spacing and high-frequency sources suggest that the wide-angle reflections from the Moho arise from short discontinuous reflectors instead of a sharp first-order discontinuity/boundary similar to vertical reflection studies (Long et al, 1994). These laterally discontinuous bright lower-crustal reflections are modeled as a lamellar structure with a stack of thin layers (1-to 5-km long and 100-to 500-m thick) of alternating high and low velocities (Krishna & Vijaya Rao, 2011;Sandmeier & Wenzel, 1986). Alternatively, such a complex lower-crustal reflectivity can be modeled by a medium of random distribution of scatterers (Gibson & Levander, 1988).…”
Section: Lower Crust and Reflection Mohomentioning
confidence: 89%
See 1 more Smart Citation
“…Contrarily, high-resolution refraction studies with 50-to 100-m shot spacing and high-frequency sources suggest that the wide-angle reflections from the Moho arise from short discontinuous reflectors instead of a sharp first-order discontinuity/boundary similar to vertical reflection studies (Long et al, 1994). These laterally discontinuous bright lower-crustal reflections are modeled as a lamellar structure with a stack of thin layers (1-to 5-km long and 100-to 500-m thick) of alternating high and low velocities (Krishna & Vijaya Rao, 2011;Sandmeier & Wenzel, 1986). Alternatively, such a complex lower-crustal reflectivity can be modeled by a medium of random distribution of scatterers (Gibson & Levander, 1988).…”
Section: Lower Crust and Reflection Mohomentioning
confidence: 89%
“…There are some limitations to migrate the deep crustal seismic data due to the short length of reflectors, low S/N ratio, and difficulty in deriving the appropriate velocity model (Warner, 1987). The velocity model for the Delhi fold belt region (Figure 1b), which is located just 50 km to the west of the present profile, is used as the initial velocity model for migration (Krishna & Vijaya Rao, 2011). Refraction/wide-angle reflection studies in the Son Valley Vindhyan basin revealed 4.8 and 5.1-5.3 km/s as the upper and lower Vindhyan velocities, respectively (Kaila et al, 1989).…”
Section: Data Processingmentioning
confidence: 99%
“…These wide-angle reflections are successfully modeled similarly as the SE-dipping reflectors (Fig. 4) revealed in the near-vertical reflection section (Krishna and Vijaya Rao, 2011). The velocity-depth model of the region (Fig.…”
Section: Deep Crustal Seismic Studymentioning
confidence: 95%
“…The velocity model derived from refraction/wide-angle reflection data (Krishna and Vijaya Rao, 2011) is presented in Fig. 4.…”
Section: Deep Crustal Seismic Studymentioning
confidence: 99%
See 1 more Smart Citation